Psoriasis as a risk factor of cardiovascular diseases - Komorowska, Olivia Rita; Szczerkowska-Dobosz, Aneta; Purzycka-Bohdan, Dorota; Rawicz-Zegrzda, Dorota; Dudziak, Maria (Dermatology Review/Przegląd Dermatologiczny, 2014)
Psoriasis is a chronic inflammatory skin disease associated with increased proliferation of the epidermis. Combination of genetic, immunological and environmental factors underlies the skin lesion. Until recently, psoriasis has been conceived as a skin limited disorder. Studies during the last decade revealed that psoriasis is a systemic disease which is associated with increased incidence of a many conditions, including cardiovascular diseases. It is considered that chronic inflammation, which is part of the pathogenesis of both psoriasis and vascular diseases, is responsible for it. It has been shown that psoriatic patients more often than in the general population have hypertension, atherosclerosis, dyslipidemia, diabetes and obesity. Abnormal life style of patients with psoriasis, resulting, inter alia, in social stigmas, is important for the cardiovascular risk. Because of increased cardiovascular risk factors, patients with psoriasis require interdisciplinary medical care and prevention – imaging studies of the heart and blood vessels.